38. Uluslararası Türk tıp tarihi kongresi : İstanbul Arkeoloji Müzeleri geçmişten günümüze tıp sergisi = 38th international congress on history of medicine : Istanbul Archeological Museums, medical exhibition from past to present. (İstanbul)
118 s.